LOCAL ECONOMIC DEVELOPMENT AS AN IMPLICATION OF UNIVERSITY EXISTENCE Case Study: University of Brawijaya Neighborhood - MAULANA ROBBIDIEN; Shofwan , SE., M.Si (Jurnal Ilmiah Mahasiswa FEB, 2014)
Brawijaya University is one of the best universities in Malang City. The existence of Brawijaya University is believed to be able to improve the prosperity of local community by creating the work opportunity and increasing the people's income. The local community of the university provides the primary need of college students (clothes, foods, and services) in order to get more income. This research used the qualitative method with in-depth interview approach on the informant. The research took 75 informants; they were 25 owners of boarding houses, 25 owners of restaurants, 25 service providers (photo copy, laundry, etc.). From these 75 informants, only 25 of them were interviewed in depth. The research shows the result that the existence of Brawijaya University brings the multiplier effect. The existence of Brawijaya University causes new activities around it and it is perceived positive by the local community. It is proven by the responses from all informants who agree that the existence of Brawijaya University improves their prosperity and income and absorbs the labors around it. Keywords: University, Prosperity, Local Economic Development, Multiplier Effect